(untitled) (Revista de História Regional, 2025)
Brazil, particularly the Northern region, is characterized by significant heterogeneity in the living and working conditions of rural youth. In the Amazonian riverine areas, this diversity is reflected in varying forms of productive engagement, limited access to public services, and distinct patterns of sociability. The lack of employment and income opportunities, combined with the absence of public policies targeting youth, limits their ability to plan and pursue life projects. Açaí, a fruit of great economic and social importance to the region, requires a thorough analysis of its production chain. The growing demand for this product, without proper attention to safety and the quality of life of the communities involved, has severe consequences. This study examines the precarious working conditions of young riverine workers in the açaí production chain, considering factors such as rural poverty, insufficient education, and a lack of opportunities for decent work. The exploitation of unskilled labor, low wages, informality, and the absence of social dialogue undermine these young workers’ full citizenship. The research, conducted in the community of Rio Quianduba in the municipality of Abaetetuba, Pará, concludes that açaí harvesting imposes risks and hardships that violate the fundamental rights of young people, which are not acknowledged by other actors in the production chain or by end consumers. This scenario reflects a hegemonic discourse about the Amazon that perpetuates inequalities, negatively affecting the construction of youth identity and their ability to develop life projects that express their subjectivities in contemporary times.